PENTINGNYA PENDAMPINGAN HUKUM BAGI KORBAN TINDAK PIDANA KEKERASAN SEKSUAL: KEBUTUHAN DAN KEHARUSAN HUKUM PIDANA - Ridwan, Fihra Rizqi Novia; Yustia, Dewi Asri (Universitas Muhammadiyah Ponorogo, 2024)
The number of cases of sexual violence that is currently occurring is getting higher and more extreme. It occurs due to the inability to handle the case. The researcher used a normative juridical research method with a qualitative juridical approach; namely, the obtained data was analyzed using a legal theory approach, legal principles, and a statutory approach. She conducted library research and field research. She conducted interviews with experienced victim advocates with a victim's perspective at the Legal Aid Institution of the Indonesian Women's Association for Justice Jakarta. She analyzed the problem of legal aid for victims of criminal acts of sexual violence using approaches to legal theory, legal principles, and statutory regulations. The legal materials used to analyze the issue were primary legal materials, secondary legal materials, and tertiary legal materials through scientific journals, statutory regulations, and other relevant legal literature. The research results indicated that there are many serious obstacles and challenges faced by victims of sexual violence, such as law enforcement, lack of understanding by law enforcement officials regarding victims' rights, criminalisation of victims, and difficulties for victims in accessing support services. Therefore, assisting victims of sexual violence is very important to increase the understanding and awareness of law enforcement officials regarding victims' rights as well as providing adequate safe space for victims in dealing with their cases.